Asuhan Keperawatan pada Ny.Z dengan Post Operasi Ekstraksi Katarak Ekstrakapsular (EKEK) Indikasi Katarak Senilis di Ruang Mawar 2 RSUD Dr.Soeselo Kabupaten Tegal - Muhammad Farhan; Ahmad Zakiudin; Tati Karyawati (STIKES Columbia Asia Medan, 2024)
The eye is one of the main human visual organs whose function is to convert stimuli into visual perception. This organ is very sensitive and susceptible to various disorders. The eyes are a visual organ that allows us to observe the environment around us, obtain information and carry out various daily activities (Ameliany, 2022). Cataracts can be classified based on their severity into incipient, immature, mature and hypermature cataracts. Apart from that, cataracts can also be differentiated based on the age at which they appear, namely congenital, juvenile, presenile and senile (Khairunnisa, 2023).